Answer :

As we know cosec(–θ) = –cosecθ


cosec = –cosec


–cosec can be written as –cosec


Also,


cosec(2π+θ) = cosecθ


–cosec = –cosec


As we know –cosec(θ) = cosec(–θ)


–cosec = cosec


Now the question becomes cosec–1(cosec)


cosec–1(cosec x) = x


Provided x ϵ –{0}


we can write cosec–1(cosec.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

State True or FalMathematics - Exemplar

State True or FalMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Find the principaRD Sharma - Volume 1

State True or FalMathematics - Exemplar

State True or FalMathematics - Exemplar